PENGARUH MEDIA PEMBELAJARAN BERBASIS GAME EDUKASI WORDWALL TERHADAP MOTIVASI PESERTA DIDIK PADA MATA PELAJARAN IPAS DI KELAS VI UPT SPF SD INPRES BORONG JAMBU III KOTA MAKASSAR - Yustari; Hakim, Abdul; Sayidiman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study is a quantitative study with a research design using a quasi experiment. This study aims to determine the description of the use of learning media based on wordwall educational games in IPAS subjects in class VI UPT SPF SD Inpres Borong Jambu III Makassar city. Then find out the description of student learning motivation in IPAS subjects in class VI UPT SPF SD Inpres Borong Jambu III Makassar City and knowing the effect of the use of learning media based on wordwall educational games on student learning motivation in IPAS subjects in class VI UPT SPF SD Inpres Borong Jambu III Makassar City. The population in this study amounted to 50 students, consisting of 25 students in class VI A and 25 students in class VI B. The sample used was 25 students from class VI B who were selected through random sampling. Data collection was done through questionnaires, observation and documentation. The research data were analyzed using descriptive statistics and inferential analysis. The results of descriptive analysis research show that the utilization of learning media based on wordwall educational games has a great influence on student learning motivation. In addition, inferential analysis using independent sample t-test shows a probability value smaller than 0.05. This causes the null hypothesis (Ho) to be rejected and the alternative hypothesis (Ha) to be accepted, so that it can be concluded that worwall educational game-based learning media has a significant effect on student learning motivation in IPAS subjects in grade VI elementary school.